ـــاء الإداري تنظیــــــم القض في ظل قانون13 - 22 - سلماني أسماء (المسيلة, 2023)
یتمحور هذا الموضوع ما یتعلق بالقضاء الإداري الجزائري من فترة الاستقلال لغایة هذا الیوم والتوجهات التي طرأت علیه ،وحول تنظیم القضاء الإداري في ظل القانون المتعلق بالإجراءات المدنیة الإداریة لسنة 2022 ، والذي جاء من خلاله إلى تحقیق أهم مبدأ وهو التقاضي على درجتین . وتظهر أهم المستجدات التي جاء بها القانون والمتعلقة بصفة خاصة بالقضاء الإداري ، من خلال ما نص علیه دستور 2020،إذ جاء بإنشاء المحاكم الإداریة للاستئناف ،وما تبعه من إصدار الأخیر للقانون 13 -22 والذي بدوره جسده بصفة صریحة وتحقیقا للمبدأ السابق ذكره ،وما سبقه من إصدار قوانین المتعلقة بالتنظیم والتقسیم القضائیان وما لحقه من مراسیم . بالإضافة إلى الحدیث عن المستجدات في المادة الإداریة والتي تظهر من خلال الاعتماد على الإحالة فیما یتعلق بإجراء رفع الدعوى أمام هذه المحكمة المستحدثة ، ٕوالغاء وجوب المحامي أمام المحكمة الإداریة مع و إلزامیته أمام الاستئناف ، ٕواجراء رفع الدعوى إلكترونیا أو تقلیدي. Abstract: This subject focuses on Algeria's administrative justice from the period of independence to the present day and the trends that have arisen. The organization of the administrative judiciary under the Law on Administrative Civil Procedure of 2022, through which it came to achieve the most important principle of Litigation on two levels. The most important developments in the law, particularly those relating to administrative justice, are reflected in the provisions of the Constitution of 2020, which provide for the establishment of administrative courts of appeal, The subsequent enactment of Act No 22-13, which in turn explicitly embodied it in pursuit of the aforementioned principle, the earlier enactment of laws on judicial regulation and division, and the subsequent decrees. In addition to talking about the developments in the administrative article, which appear by relying on the referral in relation to the procedure of filing the case before this new court , and eliminating the obligation of counsel to appeal, and the procedure of filing the case electronically or traditionally
Keywords: ـــاء الإداري تنظیــــــم القض في ظل قانون13 - 22